2000
DOI: 10.1021/cm990799h
|View full text |Cite
|
Sign up to set email alerts
|

C60-Containing Poly(1-phenyl-1-alkynes):  Synthesis, Light Emission, and Optical Limiting

Abstract: While polymerizations of 1-phenyl-1-propyne (PP) and 1-phenyl-1-butyne (PB) initiated by WCl 6 -Ph 4 Sn at room temperature yield small amounts of polymers (0.05-5.3%) with low molecular weights (M n 8000-15000) and high polydispersity indexes (PDI up to 109), addition of C 60 into the initiator mixture dramatically boosts its catalytic activity, producing polymers with high M n s (up to 171 000) and low PDIs (down to 2.2) in high yields (up to 99.5%). The resultant polymers are soluble, stable, and film-formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 80 publications
(76 reference statements)
6
48
0
Order By: Relevance
“…In 2000 the star shaped C 60 containing poly(1-phenyl-1-butyne) 16 turned out to be stable, and film-forming with a fullerene content of up to 9.1 wt%. NLO studies revealed that at 532 nm (Nd:YAG laser) 16 shows improved optical limiting performances compared to C 60 in solution at a linear transmission of 43% [104]. In the same year the side chain polyfullerene 17, prepared by Friedel-Crafts addition of C 60 and of a C 60 -derivative to a polycarbonate, also displayed good optical limiting properties [105].…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…In 2000 the star shaped C 60 containing poly(1-phenyl-1-butyne) 16 turned out to be stable, and film-forming with a fullerene content of up to 9.1 wt%. NLO studies revealed that at 532 nm (Nd:YAG laser) 16 shows improved optical limiting performances compared to C 60 in solution at a linear transmission of 43% [104]. In the same year the side chain polyfullerene 17, prepared by Friedel-Crafts addition of C 60 and of a C 60 -derivative to a polycarbonate, also displayed good optical limiting properties [105].…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Our group has done a pioneering work in wrapping CNTs with conjugated polymers. In 1999, our group successfully prepared PPA/CNT nanohybrid by in situ polymerization technique [81], and thereafter established a platform to prepare a series of PA/CNT and PA/C 60 nanohybrids by physical and chemical methods as shown in Scheme 1.8 [82,83].…”
Section: Optical Nonlinearitymentioning
confidence: 99%
“…The data for the parent forms, that is, PPA and C 60 , are given in the same figure for comparison [81,83]. When a THF solution of PPA is shot by the 8-ns, 532-nm laser light, the transmitted fluence linearly increases in the region of low incident fluence (linear transmittance 75%).…”
Section: Optical Nonlinearitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the nonlinear refractive coefficients of the hybrids can be determined with equation(3). In accordance with the observed b and n 2 values, the third-order susceptibility c (3) value can be calculated with the following equation[32]:…”
mentioning
confidence: 99%